Mineralogical characteristics of slag (from the Flotation plant of RTB Bor) granulated in the laboratory conditions - Ljubojev Vesna; Marjanović Vesna; Milanović Dragan; Stanković Suzana (Mining and Metallurgy Engineering Bor, 2015)
A sample of slag from the Flotation Bor, RTB Bor, was mineralogical tested after granulation in the laboratory conditions. Minerals contained in the sample of granulated slag are: fayalite and ferrite that form the basis with rarely sprayed fine particles of magnetite, pyrite, chalcopyrite, bornite, copper matte and elemental - native copper [6, 7]. Granulation of slag was conducted in the laboratory conditions on the device specially designed for this purpose.